SMEs in the construction sector: cases of the Indonesia European Union comprehensive economic partnership agreement. (9th June 2022) - Bawono, Indro; Maulina, Erna; Rizal, Muhamad; Purnomo, Margo
The Indonesian government and the European Union have signed a free trade agreement under the Indonesia-European Union comprehensive economic partnership agreement (IEU-CEPA). This agreement includes, among others, trade in goods and services, investment, and government procurement. The IEU-CEPA provides access for SMEs, especially in the construction sector, to market their products. This article discusses the readiness of SMEs in the construction sector to access government procurement using knowledge, motivation, opportunity, and risk as variables. Based on the partial least square-structural equation modelling, the study shows that most construction SMEs are not ready to access government procurement with partner countries. Risk is the most critical factor that has the most significant influence on SMEs readiness to compete at the international level.